Encyclopedia of capitalism - Hussain, Syed B. (New York : Facts On File, 2004)
Examines all aspects of capitalism, including its history, philosophy, theories, key thinkers, and the impact on individual countries. It comprises approximately 750 authoritative entries dealing with the rise and development of capitalism from Adam Smith onward.
Includes bibliographical references and index.
oif 11/07/2018
Ref.
Keywords: Capitalism---Encyclopedias